Cardiac arrest after pulmonary aspiration in hospitalised patients: a national observational study. Issue 3 (19th March 2020) - Albert, Malin; Herlitz, Johan; Rawshani, Araz; Ringh, Mattias; Claesson, Andreas; Djärv, Therese; Nordberg, Per
Abstract : Objective: To study characteristics and outcomes among patients with in-hospital cardiac arrest (IHCA) due to pulmonary aspiration. Design: A retrospective observational study based on data from the Swedish Registry of Cardiopulmonary Resuscitation (SRCR). Setting: The SRCR is a nationwide quality registry that covers 96% of all Swedish hospitals. Participating hospitals vary in size from secondary hospitals to university hospitals. Participants: The study included patients registered in the SRCR in the period 2008 to 2017. We compared patients with IHCA caused by pulmonary aspiration (n=127), to those with IHCA caused by respiratory failure of other causes (n=2197). Primary and secondary outcome measures: Primary outcome was 30-day survival. Secondary outcome was sustained return of spontaneous circulation (ROSC) defined as ROSC at the scene and admitted alive to the intensive care unit. Results: In the aspiration group 80% of IHCA occurred on general wards, as compared with 63.6% in the respiratory failure group (p<0.001). Patients in the aspiration group were less likely to be monitored at the time of the arrest (18.5% vs 38%, p<0.001) and had a significantly lower rate of sustained ROSC (36.5% vs 51.6%, p=0.001). The unadjusted 30-day survival rate compared with the respiratory failure group was 7.9% versus 18.0%, p=0.024. In a propensity score analysis (including variables; year, age, gender, location of arrest, initial heart rhythm, ECG monitoring, witnessed collapse and a previous medical history of; cancer, myocardial infarction or heart failure) the OR for 30-day survival was 0.46 (95% CI 0.19 to 0.94). Conclusions: In-hospital cardiac arrest preceded by pulmonary aspiration occurred more often on general wards among unmonitored patients. These patients had a lower 30-day survival rate compared with IHCA caused by respiratory failure of other causes.